Perceived crime and traffic safety is related to physical activity among adults in Nigeria - Oyeyemi Adewale L; Adegoke Babatunde O; Sallis James F; Oyeyemi Adetoyeje Y; De Bourdeaudhuij Ilse (BMC, 2012)
Abstract Background Neighborhood safety is inconsistently related to physical activity, but is seldom studied in developing countries. This study examined associations between perceived neighborhood safety and physical activity among Nigerian adults. Methods In a cross-sectional study, accelerometer-based physical activity (MVPA), reported walking, perceived crime and traffic safety were measured in 219 Nigerian adults. Logistic regression analysis was conducted, and the odds ratio for meeting health guidelines for MVPA and walking was calculated in relation to four safety variables, after adjustment for potential confounders. Results Sufficient MVPA was related to more perception of safety from traffic to walk (OR=2.28, CI=1.13- 6.25) and more safety from crime at night (OR=1.68, CI=1.07-3.64), but with less perception of safety from crime during the day to walk (OR=0.34, CI=0.06- 0.91). More crime safety during the day and night were associated with more walking. Conclusions Perceived safety from crime and traffic were associated with physical activity among Nigerian adults. These findings provide preliminary evidence on the need to provide safe traffic and crime environments that will make it easier and more likely for African adults to be physically active.